LIQUID CHROMATOGRAPHY–MASS SPECTROMETRY ANALYSIS OF FRUITS OF AN ECONOMICALLY IMPORTANT PLANT SCHISANDRA CHINENSIS BAIL. FROM CHINA AND EAST RUSSIA - An, Luferov; Nv, Kartashova; Av, Strelyaeva; Rm, Kuznetcov (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The study was carried out with an objective to characterize the possible bioactive phytochemical constituents from fruits of Schisandra chinensis Bail. by liquid chromatography–mass spectrometry analysis. Methods: Plant material was collected from Schisandra chinensis during August–October. The dried plant fruits were extracted with solvents using ethanol 95% extractor. The results of chromatography–MS analysis performed on the instrument Agilent Technologies established the presence of major and minor components. It was conducted a qualitative and quantitative comparison of infusions using software ChemStationE 02.00 and full library of mass spectra NIST 05.